Status of Sodium Nitrite in Meat and Meat Products Available in the Market of Kathmandu, Nepal - Pradhan, Hareram; Poudel, Sabitri; Bokkhim, Huma; Rai, Krishna Prasad; Karn, Sanjeev Kumar (Journal of Food Science and Technology Nepal, 2019)
Sodium nitrite was determined in 64 meat and meat products available in National Food and Feed Reference Laboratory from July 2017 to June 2018 following the AOAC (2016). None of the samples exceeded the Government of Nepal and India standard (200 ppm) and approximately five percent of the total samples had crossed the European Union standard (150ppm). Highest range (1.49-165.72 ppm) of sodium nitrite was found in chicken sausages and lowest (Not detected-55.83 ppm) in miscellaneous products (meat pickle, mo:mo, kebab, dried meat, and claws) .Chicken and buff sausages were spiked at 50, 100 and 200 ppm level and the recovery were found to be 84.32, 94.97, 89.97 and 99.84, 104.36, 105.99% respectively. Overall recovery were significantly higher (p=0.000) in buff sausage (103.40 ± 3.57%) than in chicken sausage (89.75 ± 4.79 %) at 5% level of significance. Sodium nitrite in the quality control sample was found to be 162.5±1.08 ppm which was within the range (138-226ppm) given by the supplier.